The Relevance of Liberal Arts in the Digital Age: A Literature Review - Elisabet Marthawati Samosir; Danny Philipe Bukidz (Indonesian Journal of Educational Science and Technology, 2023)
In an increasingly advanced digital era, the need for technical skills in the world of education has become a major highlight. Specialization-based education is the focus in higher education. In this situation, Liberal Arts education also has a very important role in developing cross-disciplinary skills and human skills holistically. This article aims to investigate the relevance of Liberal Arts education in the digital era and try to identify how Liberal Arts education can make a contribution to higher education in facing the challenges of the digital age. This research uses a qualitative approach by conducting a literature review of various relevant sources regarding Liberal Arts education and developments in the digital era. The articles analyzed included five scientific articles originating from research journals. This qualitative approach allows the author to present a comprehensive picture of the relevance of Liberal Arts education in the digital era. The results found by the author through these articles state that Liberal Arts education has an important role in preparing students to face the complexities of the digital era. The critical skills, systemic thinking, effective communication and professional ethics taught in Liberal Arts education provide a strong foundation for students.